The workshop-laboratory as an unavoidable condition in the training of industrial engineer - Mejía Correa, Juan José Alberto; Bermúdez Sarguera, Rogelio; Pentón Quintero , Aylín; Mejía Pérez , Juan Francisco (Revista Minerva, 2024)
In the article, we describe a methodological proposal for carrying out professional practice, assuming the workshop-laboratory as a form of teaching organization, an unavoidable requirement for the training and development of the skills and habits required by the Industrial Engineer, depending on their graduation profile. As a precursor action, we characterized the degree of pedagogical preparation that the teachers of the Veracruz Technological Institute had and the knowledge of the methodology, in the use of the workshop as a form of teaching organization. In addition, the study plan of the Industrial Engineering degree was analyzed to assess the systematicity of the skills declared in the subject programs that made up the Industrial Engineer curriculum, in the different semesters. The fundamental result indicated that the mastery of the instrumentations studied is at a medium-high level, which correlates with the structuring of the subject programs that does not favor the development of said instrumentations.